Molecular ruthenium water oxidation catalysts carrying non-innocent ligands: mechanistic insight through structure–activity relationships and quantum chemical calculations. Issue 5 (12th November 2015) - Kärkäs, Markus D.; Liao, Rong-Zhen; Laine, Tanja M.; Åkermark, Torbjörn; Ghanem, Shams; Siegbahn, Per E. M.; Åkermark, Björn
Abstract : Herein is highlighted how structure–activity relationships can be used to provide mechanistic insight into H2 O oxidation catalysis. Abstract : Robust catalysts that mediate H2 O oxidation are of fundamental importance for the development of novel carbon-neutral energy technologies. Herein we report the synthesis of a group of single-site Ru complexes. Structure–activity studies revealed that the individual steps in the oxidation of H2 O depended differently on the electronic properties of the introduced ligand substituents. The mechanistic details associated with these complexes were investigated experimentally along with quantum chemical calculations. It was found that O–O bond formation for the developed Ru complexes proceeds via high-valent Ru VI species, where the capability of accessing this species is derived from the non-innocent ligand architecture. This cooperative catalytic involvement and the ability of accessing Ru VI are intriguing and distinguish these Ru catalysts from a majority of previously reported complexes, and might generate unexplored reaction pathways for activation of small molecules such as H2 O.